MENINGKATKAN KEMAMPUAN MEMBACA AWAL SISWA MELALUI PERMAINAN BAHASA DI KELAS 1 SDN 012 SIMANGAMBAT KECAMATAN SIABU KABUPATEN MANDAILING NATAL - Nurlohot Nurlohot (Universitas Negeri Medan, 2017)
Abstract : Improving Student's Early Reading Ability through Language Game in Class I SDN 012 Simangambat Kecamatan Siabu Kabupaten Mandailing Natal. The purpose of this study is to improve student learning outcomes and reading ability of first grade students in learning Indonesian language. Classroom Action Research is conducted in 2 cycles. The subjects of this study were IB IB SDN 012 Simangambat students with 22 students consisting of 12 male students and 10 female students. The results showed that the application of game language can improve student learning outcomes. Learning outcomes at prasiklus, the ability to read exactly 2 people, put the pause 10 people, read smooth 5 people, distinguish the sound of 16 people, and understand the meaning of 11 people. In the first cycle the students' ability increased to: read a simple sentence of 7 people, put the pause 11 people, read smoothly 8 people, distinguish the sound of 18 people, and understand the meaning of the word increased to 13 people. In the second cycle, the students' ability increased again to: read a simple sentence of 9 people, put the pause 14 people, read smoothly 10 people, distinguish the sound of 20 people, and understand the meaning of the word 15 people.Keywords : Early Reading Abilities, Game Language, IndonesianAbstrak : Meningkatkan Kemampuan Mambaca Awal Siswa Melalui Permainan bahasa di Kelas I SDN 012 SimangambaT Kecamatan Siabu Kabupaten Mandailing Natal. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar siswa dan kemampuan membaca awal siswa kelas I dalam pembelajaran bahasa Indonesia. Penelitian Tindakan Kelas ini dilaksanakan dalam 2 siklus. Subjek penelitian ini adalah siswa kelas IB SDN 012 Simangambat dengan jumlah 22 orang terdiri dari 12 siswa laki-laki dan 10 siswa perempuan. Hasil penelitian menunjukkan bahwa penerapan permainan bahasa dapat meningkatkan hasil belajar siswa. Hasil belajar pada saat prasiklus, kemampuan membaca tepat hanya 2 orang, menempatkan jeda 10 orang, membaca lancar 5 orang, membedakan bunyi 16 orang, dan memahami makna 11 orang. Pada siklus I kemampuan siswa meningkat menjadi: membaca kalimat sederhana 7 orang, menempatkan jeda 11 orang, membaca lancar 8 orang, membedakan bunyi 18 orang, dan memahami makna kata meningkat menjadi 13 orang. Pada siklus II, kemampuan siswa meningkat lagi menjadi: membaca kalimat sederhana 9 orang, menempatkan jeda 14 orang, membaca lancar 10 orang, membedakan bunyi 20 orang, dan memahami makna kata 15 orang.Kata Kunci: Kemampuan Membaca Awal, Permainan Bahasa, Bahasa Indonesia